FACTOR AFFECTING SELF-COMPASSION OF TEACHER PROFESSION STUDENTS - Deesom , Neenara; Praabsri, Pikun; ketsanoi , Siriporn; vanaporn , Sirilak; Koolnapadol, Aungkana (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were to compare the factors of birth order, marital status of parents, guardians and household income that affect the Self- compassion of Teacher profession students by using a descriptive research design. Population was the 3,693 students of Bachelor of Teaching Program, Surindra Rajaphat University, semester 2, academic year 2021. The sample group used in this study consisted of 400 people by simple randomization method. The Instrument was developed from The Self-compassion Scale (SCS) which has 26 items 6 components consists of Self – Kindness, Self – judgement, Common Humanity, Sef – Isolation, Mindfulness and Over – identification which was 5 level rating scale. The reliability was examined by 3 experts for consistenced index between question and research objective, then selected a question with IOC at 0.5 or higher. Validily was determined by using The Cronbach’s alpha coefficient of conformity method to obtain a validity value of .85. Data analyzed by F - test. The results founded that the factors that affect the Self- compassion of Teacher profession students were marital status of parents and the guardians significantly at the .05 level. When classified by aspects, it was found that the marital status of the parents had 2 components that the students had different averages of Self-compassion, Self - Kindness and Self - Isolation. Guardians found that all 6 components different. However, the factors of birth order and household income were not different.